2017
DOI: 10.1007/s00432-017-2553-9
|View full text |Cite
|
Sign up to set email alerts
|

Taxane, platinum and 5-FU prior to chemoradiotherapy benefits patients with stage IV neck node-positive head and neck cancer and a good performance status

Abstract: With prophylactic antibiotics and granulocyte colony-stimulating factor TPF was well tolerated with good survival outcomes. TPF should remain a treatment option for stage IV neck node-positive patients with a good performance status. The use of tumour grade to aid patient selection for TPF warrants investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Platinum-based combination chemotherapy regimens have been widely used in clinical practice. In recent years, a number of clinical trials have confirmed that TPF regimen (docetaxel, cisplatin and 5-fluorouracil) may achieve a higher rate of remission without significantly increasing severe adverse reactions (2,(8)(9)(10). Currently, TPF regimen is becoming the first choice of ICT for locally advanced SCCHN.…”
Section: Discussionmentioning
confidence: 99%
“…Platinum-based combination chemotherapy regimens have been widely used in clinical practice. In recent years, a number of clinical trials have confirmed that TPF regimen (docetaxel, cisplatin and 5-fluorouracil) may achieve a higher rate of remission without significantly increasing severe adverse reactions (2,(8)(9)(10). Currently, TPF regimen is becoming the first choice of ICT for locally advanced SCCHN.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, a combination between platinum, taxanes, and fluorouracil (TPF) is considered to be the optimal treatment, with superior results in induction both compared to the platinum–fluorouracil regimen and compared to the platinum–taxane combination. Haddad et al mention the benefit of the TPF regime in survival and in the preservation of the organ, being recommended both for cases with a poor prognosis and for reducing the risk of distant metastases or loco-regional failure in operable cases or those with a good prognosis [ 26 , 27 , 28 ].…”
Section: The Multidisciplinary Approach In Locally Advanced Hnc: Chal...mentioning
confidence: 99%